CircRNAs and its relationship with gastric cancer - Fang, Xinxin (J Cancer, 2019)
Circular RNAs (circRNAs), as a type of tissue specific RNA with more stable structure than linear RNAs, was poorly understood on its correlation with gastric cancer (GC). In this review, we outline the synthesis and characteristics of circRNAs and generalize their categories and functions. Through comprehensive analysis of the reported results, we find that circRNAs not only participate in the regulation of gastric cancer (GC) cell biological behaviors, such as proliferation, invasion, migration and epithelial mesenchymal transition (EMT), but also are related to the clinicopathological features of GC such as tumor differentiation, TNM stage and metastasis, etc. According to the present screening and verification results, circRNAs are suggested to be used as biomarkers for the early diagnosis and prognosis prediction of GC, and those circRNAs involved in the genesis and development of GC have the potential as novel targets for the individualized treatment of GC.